B-cell dynamics during experimental endotoxemia in humans. Issue 5 (17th May 2019) - Brinkhoff, Alexandra; Zeng, Ye; Sieberichs, Annette; Dolff, Sebastian; Shilei, Xu; Sun, Ming; Engler, Harald; Benson, Sven; Korth, Johannes; Schedlowski, Manfred; Kribben, Andreas; Witzke, Oliver; et al.
Abstract : Recently, B cells with regulatory functions suppressing T-cell immunity were identified. Inflammation in the context of sepsis is characterized by a profound immune dysfunction increasing the patient's risk for additional infections. The impact of endotoxemia on B-cell dynamics, regulatory B cells (Breg) and its contribution to immune dysfunction is unknown. It is the aim of the present study to characterize the dynamics of the B-cell compartment and Breg in an experimental human endotoxemia model. In this randomized placebo-controlled cross-over study, 20 healthy males received an intravenous injection of endotoxin ( Escherichia coli lipopolysaccharide, LPS, 0.8 ng/kg body weight) or placebo (saline 0.9%) on two otherwise identical study days. B cells were analyzed by flow cytometry at baseline and repeatedly up to 72 h after endotoxin/placebo injection. Absolute CD19 + B cells counts showed a significant decrease 3 h after endotoxin injection. Memory B cells were partially depleted from the circulation; the total number of Breg was significantly diminished 3 h after LPS challenge. Production of anti-inflammatory interleukin (IL)-10 (IL-10) by Breg was unaltered after LPS challenge. Systemic B-cell activating factor (BAFF) levels were significantly increased with a maximum after 24 h and remained increased up to 72 h post-injection. Endotoxemia causes a transient depletion of memory B cells and Breg from the circulation. However, the functional capacity of B cells to produce IL-10 is not impaired.